Construction of Da'wah in Social Media - Muhtar, Alvin Afif (SINDA: Comprehensive Journal of Islamic Social Studies, 2024)
Advances in technology, information and communication are inevitable. The use of social media is commonplace in everyday life. Making information on social media as a reference for knowledge is something that is possible and is often found, one of which is religious knowledge. Opportunities for da'wah through social media are an alternative for da'I to mad'u. For anyone who wants to preach through social media, of course, they must know and understand the construction or concept. Da'wah construction in general includes methods, strategies and tactics or execution. Meanwhile, the construction of da'wah on social media includes instruments or tools used by understanding the characteristics of social media after that understanding and using the platform or design of social media to be used. Gayeng Santri created a new perspective in preaching through social media by popularizing KH. Ahmad Bahaudin Nursalim (Gus Baha). The da'wah strategy carried out by Santri Gayeng is to upload Gus Baha's recitation content two or even three times a day. Create click bait so that viewers are curious about the content and add keywords.